Faktor–Faktor yang Mempengaruhi Keputusan Berwirausaha pada Anggota HIPMI PT Bandar Lampung: Sebuah Analisis Empiris - Viola De Yusa; Riyadini Riyan Utami; Sri Rahayu (Studi Ilmu Manajemen dan Organisasi, 2024)
Purpose: The research aims to determine the analysis of factors that influence entrepreneurial decisions among members of HIPMI PT Bandar Lampung.Methodology: The type of research used in this research is qualitative research. The population in this research is 139 students who are members of HIPMI PT Bandar Lampung, with a sample of 85 respondents using a non-probability sampling method using purposive sampling technique. The analysis tool uses the SPSS program version 25. The analysis tool used is the Cochran Q Test.Results: The research results show that there are 11 factors that influence entrepreneurial decisions among HIPMI PT Bandar Lampung members, namely the dream of being successful, a supportive family, high market demand, family background, surrounding groups, idol figures, proud of independence, HIPMI seniors, able implement his imagination, act innovatively, capital provided by the family.Conclusions: 11 factors that influence the entrepreneurial decisions of HIPMI PT Bandar Lampung students, consisting of 3 Entrepreneurial Knowledge factors, 2 Motivation factors, and 6 Reference Group factors. The most dominant factor is the Reference Group with 6 factors, such as family support, senior influence, and idol figures. These factors are important to consider in making entrepreneurial decisions.Limitations: This research contributes to HIPMI PT members being able to change their mindset about entrepreneurship and increasing entrepreneurial decisions among HIPMI PT Bandar Lampung members to open new job opportunities to reduce the unemployment rate among post-graduation students.